2018
DOI: 10.1002/mds.108
|View full text |Cite
|
Sign up to set email alerts
|

β2‐adrenoceptor agonists and antagonists and risk of Parkinson's disease

Abstract: Background: β2‐adrenoreceptors have recently been identified as regulators of the α‐synuclein gene, which is implicated in the pathogenesis of Parkinson's disease. Objective: The objectives of this study were to assess the association between use of β2‐agonists and β‐antagonists and the risk of developing PD. Methods: We conducted a nested case‐control study in a cohort of 1,762,164 adults without a diagnosis of PD. They were identified on January, 1, 2004, from the electronic medical records of the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 22 publications
6
79
0
1
Order By: Relevance
“…Their results were consistent when the latency period was extended to five and 8 years. However, their findings should be interpreted with caution because comparisons were made across multiple drugs (n=>10), which might inflate the false‐positive rate 13 . Moreover, neither study considered the competing risk of death.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Their results were consistent when the latency period was extended to five and 8 years. However, their findings should be interpreted with caution because comparisons were made across multiple drugs (n=>10), which might inflate the false‐positive rate 13 . Moreover, neither study considered the competing risk of death.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, their study only examined salbutamol use and only adjusted for age, sex and education 6 . A more rigorous, nested case‐control study found that the 2‐year PD risk was reduced by 11% to 51% for use of various types of β 2 ‐agonists in a large healthcare institute in Israel, controlling for rurality, major chronic conditions, smoking, alcohol consumption and the use of various cardiovascular drugs 13 . Their results were consistent when the latency period was extended to five and 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the study of the association between β2‐adrenoceptor agonist and antagonist exposure and the risk of Parkinson's disease (PD), by Gronich and colleagues . The good news is that beta‐receptor agonists might be protective for PD; however, neurologists will be worried by data that suggest exposure to nonselective β2‐adrenoceptor antagonists, particularly propranolol, increases the risk for PD by 2.6 times.…”
mentioning
confidence: 99%
“…We read with great interest the article by Gronich and colleagues on the effects of β2‐adrenoceptor agonists and antagonists on the risk of Parkinson's disease (PD). This case‐nested study in a large population of adults without PD followed for over 13 years showed that use of propranolol appears to be associated with an increased risk of PD, whereas use of β2‐agonists is associated with a decreased risk of PD.…”
mentioning
confidence: 99%